A Divergence of Interests: Critical Race Theory and White Privilege Pedagogy. Issue 1 (January 2020) - Crowley, Ryan M.; Smith, William L.
Background/Context: Informed by the increasing racial disparity between the nation's predominantly White teaching force and the growing number of students of color in K–12 schools, along with the well-documented struggles that White teachers have in exploring race and racial identity, the authors critique the use of White privilege pedagogy as a strategy for promoting antiracist dispositions in White pre-service teachers. Purpose/Objective/Research Question/Focus of Study: By deploying several concepts central to critical race theory, as well as critiques that note the shortcomings of past attempts at racial reform (Brown v. Board of Education, Voting Rights Act), the authors investigate the effectiveness of White privilege pedagogy within the teacher education setting. Research Design: To construct our conceptual critique of White privilege pedagogy within teacher education, we reviewed the extant literature that discussed the range of shortcomings to this pedagogical approach. To create a more historical and structural critique, we demonstrated how the tenets of White privilege pedagogy conflicted with key principles of critical race theory and with lessons from past racial remedies. We contend that White privilege pedagogy arises from a racial liberalist worldview and requires an untenable convergence of interests that limits its long-term impact. We parallel our critiques of White privilege pedagogy with arguments used by critical race scholars to explain the limited impact of previous efforts at racial reform. Conclusions/Recommendations: The authors urge teacher educators to move away from the individualized and over-essentialized representations of racism inherent to White privilege pedagogy in favor of historical, structural, and intersectional discussions of race, racism, and the construction of White privilege.